Back blast - Greaney, Mark (Greaney, Mark. Gray Man novel., 2016)
Returning to Washington to uncover the truth about why the CIA betrayed him, former elite agent-turned-Gray Man Court Gentry discovers that the case is still very much under discussion and that he has stumbled onto a secret that powerful enemies will kill to keep.